Assistant for A. Dodworth's pupils. - Dodworth, Allen; Miniature Book Collection (Library of Congress) (New York, Nesbitt & Co., Printers, 1878)
This small, pocketsize manual was intended for the students of well-known New York dancing master and composer Allen Dodworth. The manual states the rules for classes, gives Dodworth's qualifications as a teacher, and covers manners and etiquette. This edition expands on the 1873 edition by providing more information on the waltz and the cotillon or German, for which eighty-nine figures are presented.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Ballroom dancing -- Handbooks, manuals, etc; German (Dance) -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals; Miniature books -- Specimens